The Relationship Between Microplastic Samples in Blood and The Stage of Epithelial Ovarian Cancer at Dr. M. Djamil Padang General Hospital - Annisa Anzar Aprilianti; Puja Agung Antonius; Hirowati Ali (Andalas Obstetrics And Gynecology Journal, 2026)
Introduction: Ovarian cancer is the primary cause of cancer-related mortality in women, with epithelial ovarian cancer (EOC) ranking as the second greatest cause of death among gynaecological malignancies.  The rising use of plastics has resulted in increased microplastic exposure among the population.  This exposure aligns with recognised risk factors for ovarian cancer, including genetic, hormonal, and lifestyle elements. This study aimed to investigate the relationship between microplastics in blood samples and the stage of epithelial ovarian cancer at Dr. M. Djamil General Hospital, Padang. Methods: Between August 2024 and January 2025, a cross-sectional analytical correlational investigation was carried out.  Forty individuals with histopathologically verified epithelial ovarian carcinoma were consecutively recruited.  Blood samples were examined for di(2-ethylhexyl) phthalate (DEHP) microplastics utilizing Liquid Chromatography–Mass Spectrometry (LCMS).  Data were evaluated utilizing descriptive statistics and the Chi-square test, with p < 0.05 being significant. Results: The average age of patients was 49.1±10.59 years, with the majority being multiparous, married, and of normal weight.  The histological subtypes comprised mucinous (37.5%), serous (30%), endometrioid (20%), and clear cell (12.5%).  Microplastics were identified in 30% of blood samples, with the greatest prevalence observed in mucinous (40%) and endometrioid (37.5%) subtypes. Statistical study indicated no significant correlation between microplastic occurrence and the stage of epithelial ovarian cancer (p = 0.869). Conclusion: Microplastics were identified in the blood of around one-third of patients with epithelial ovarian cancer, present across all histological subtypes. However, no substantial link was identified between the presence of microplastics and the cancer stage.